Does welfare reform affect fertility? Evidence from the UK - Mike Brewer; Anita Ratcliffe; Sarah Smith (Institute for Fiscal Studies (IFS), 2008)
In 1999 the UK government made major reforms to the system of child-contingent benefits, including the introduction of Working Families' Tax Credit and an increase in means-tested Income Support for families with children. Between 1999-2003 government spending per-child on these benefits rose by 50 per cent in real terms, a change that was unprecedented over a thirty year period. This paper examines whether there was a response in childbearing. To identify the effect of the reforms, we exploit the fact that the spending increases were targeted at low-income households and we use the (exogenously determined) education of the woman and her partner to define treatment and control groups. We argue that the reforms are most likely to have a positive fertility effect for women in couples and show that this is the case. We find that there was an increase in births (by around 15 per cent) among the group affected by the reforms.
Keywords: J13; J18; H53; 330; Welfare reform; Fertility; Working Families Tax Credit; Familienpolitik; Familienleistungsausgleich; Steuerbegünstigung; Fruchtbarkeit; Großbritannien